2020
DOI: 10.5455/medarh.2020.74.172-176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Allopurinol and Febuxostat on the Values of Triglycerides in Hyperuricemic Patients

Abstract: Introduction: Hyperuricemia is an independent risk factor for the development of many diseases. Aim: The aim of this paper is to compare the effects of allopurinol and febuxostat on the values of triglycerides and uric acid in hyperuricemic patients. Methods: This was a pharmacological-clinical retrospective-prospective study. The research sample comprised 50 examinees of both genders and different ages who were undergoing allopurinol (100 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…However, the risks for other renal outcomes were similar. In asymptomatic hyperuricemic patients without gout, febuxostat was found to reduce the risk of macroalbuminuria development or worsening [22].…”
Section: Renal Injury and Signaling Pathwaysmentioning
confidence: 96%
“…However, the risks for other renal outcomes were similar. In asymptomatic hyperuricemic patients without gout, febuxostat was found to reduce the risk of macroalbuminuria development or worsening [22].…”
Section: Renal Injury and Signaling Pathwaysmentioning
confidence: 96%
“…However, allopurinol use causes a substantial increase in triglyceride values after three and six months. Contrarily, febuxostat intake causes a noticeable decrease in TG levels for the initial three months but this decrease was not significant after six months [ 45 ]. Another study reported that febuxostat decreased serum cholesterol values effectively compared to allopurinol but both drugs’ performance was comparable in ameliorating LDL and HDL cholesterol [ 46 ].…”
Section: Reviewmentioning
confidence: 99%